The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/jp502616h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible-Light Photoactivity of CuWO4 through a Surface-Deposited CuO

Abstract: Several papers have shown that CuWO 4 is active under visible light for water oxidation at an applied potential bias and for organic degradation in an aerated aqueous suspension. In this work, we report that the observed reduction of O 2 on the irradiated CuWO 4 is a multielectron transfer process with the formation of H 2 O 2 . More importantly, the surface modification of CuWO 4 with 1.8 wt % of CuO can increase the activity by approximately 9 times under UV light and by 5 times under visible light, for phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…It was found to be 0.136, 0.071, 0.577, 0.124, 0.125, 0.235 and 0.125 V vs RHE for CuWO4/WO3·0.33H2O,CuWO4/WO3, CuWO4/Cu2O/normalCnormalunormalO, CuWO4/normalCnormalunormalO (700 °C) and CuWO4/normalCnormalunormalO (800 °C) respectively. The obtained Vfb4pt of normalCnormalunormalWnormalO4 is almost similar with fractional varation incorparation to the early reported value, due to pH of the electrolyte solution . Then, the Vfb4pt shifted to the lower value by the formation of other secondary phase, particularly the samples with low Vfb4pt were showed better photocatalytic degradation under illumination.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It was found to be 0.136, 0.071, 0.577, 0.124, 0.125, 0.235 and 0.125 V vs RHE for CuWO4/WO3·0.33H2O,CuWO4/WO3, CuWO4/Cu2O/normalCnormalunormalO, CuWO4/normalCnormalunormalO (700 °C) and CuWO4/normalCnormalunormalO (800 °C) respectively. The obtained Vfb4pt of normalCnormalunormalWnormalO4 is almost similar with fractional varation incorparation to the early reported value, due to pH of the electrolyte solution . Then, the Vfb4pt shifted to the lower value by the formation of other secondary phase, particularly the samples with low Vfb4pt were showed better photocatalytic degradation under illumination.…”
Section: Resultssupporting
confidence: 83%
“…Figure describes the schematic representation for oxidation of the nanocomposites. The CuWO4/Cu2O/normalCnormalunormalO and CuWO4/normalCnormalunormalO have showed photocathodic current, it may be due to p ‐type nature of Cu2O and CuO . To best of our knowledge, we present the PEC performance first time for CuWO4/WO3·0.33H2O,CuWO4/Cu2O and CuWO4/Cu2O/normalCnormalunormalO nanocomposites.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…[47][48][49] Although the value of E CB of CuO is usually more negative than that of single oxygen reduction, it shows an abnormal behavior of two-electron reduction ability of oxygen. Bandara et al [50] showed that CuO was able to produce H 2 O 2 under sunlight irradiation at room temperature, which was Accordingly, the storing of O 2 as H 2 O 2 via double-electron reduction process would proceed by the following reactions:…”
Section: Cuomentioning
confidence: 99%
“…They investigated the oxygen reduction reaction over In fact, multi-electron ORR is also observed in other type II heterojunction. Chen et al [79] have prepared CuWO 4 /CuO composites via hydrothermal reaction, followed by thermal treatment. Photocatalytic test showed that the surface modification of Besides type II heterojunction based metal oxides, Katsumata et al [80] have prepared g-C 3 N 4 /WO 3 composites photocatalyst and evaluated their activity via acetaldehyde degradation.…”
Section: Semiconductor/semiconductor Heterojunctionmentioning
confidence: 99%